Three-Phase Multistage System (DC-AC-DC-AC) for Connecting Solar Cells to the Grid - Mahmudreza Changizian; Ali Zakerian; Araz Saleki (Emerging Science Journal, 2017)
Inverter systems that feed electrical power from photovoltaic (PV) system into the grid must convert the direct current of the PV array into the alternating current of the grid. In many applications, it is important for a converter to be lightweight, highly reliable, input/output isolated, flexible and operable in a boost mode. These features can be achieved by using a High-Frequency inverter which involves an isolated DC-DC stage and DC-AC section, which provides AC output. This paper proposes a new three phase topology, based on multi stage converter and PV system in order to use in medium and high power applications. The Perturb and Observe (P&O) method is used for maximum power point tracking (MPPT) control of PV array. The switching control signals for three-phase inverter are provided by hysteresis control method. Also, the comparison between the proposed topology and traditional structures has been conducted and finally the simulation researches are performed in a closed-loop control system by MATLAB/Simulink software to verify the operation of the proposed structure. The results represent better performance of the introduced system over traditional topologies.